The Clinical and Pathological Characteristics That Differentiate Cases With “Low Estrogen Receptor Expression” From Triple-Negative Breast Cancer - Cem Karaali; Mümin Emiroğlu; Mustafa Değirmenci; Murat Keser; Semra Salimoğlu; Canan Kelten Talu (European Journal of Breast Health, 2024)

(untitled)
Objective: Estrogen receptor (ER) expression is an immunohistochemical marker that is examined in all invasive breast cancers and has prognostic and predictive value. ER-positive breast cancers refer to those that show positivity for ER at 1% cellular expression or higher. The American Society of Clinical Oncology/College of American Pathologists guidelines suggest using the term “low ER-positive breast cancer” for tumors with ER expression between 1% and 10%. Low ER-positive breast cancers exhibit similarities, in terms of disease-free survival and overall survival rates, to triple-negative breast cancers (TNBCs) rather than ER-positive breast cancers. In this study, our aim was to compare the clinicopathological characteristics of low ER-positive breast cancer cases diagnosed and followed in our clinic with TNBCs. Materials and Methods: A total of 26 cases of low ER-positive breast cancer diagnosed at University of Health Sciences Turkey, İzmir Tepecik Training and Research Hospital between 2010 and 2016 were retrieved from hospital records. The relevant histopathology slides and blocks were retrieved and re-evaluated retrospectively through microscopic examination. Thirteen cases that met the criteria were included in the study. Additionally, a consecutive series of 13 TNBC cases that did not receive neoadjuvant treatment within the same time period were identified. Results: In the low ER-positive group, the presence of tumor necrosis, as well as histological grade, nuclear grade and Ki-67 proliferation index were significantly lower compared to the TNBC group. Ductal carcinoma in situ (DCIS) was significantly more common in the low ER-positive group compared to the TNBC group. There were no significant differences between the two groups in terms of tumor size, histological tumor type, axillary lymph node involvement, tumor margins, peritumoral and intratumoral inflammation, local recurrence, distant metastasis, survival, and other characteristics. Conclusion: Although our study consisted of a small number of cases, some features showed significant differences between low ER-positive breast cancers and TNBCs. Histological and nuclear grades, as well as the presence of a DCIS component, were associated with low ER-positive breast cancer. In contrast, the presence of tumor necrosis, as well as Grade 3 features and a high Ki-67 proliferation index indicated TNBC.